2018
DOI: 10.3390/scipharm86020020
|View full text |Cite
|
Sign up to set email alerts
|

Host-Guest Interactions of Plumbagin with β-Cyclodextrin, Dimethyl-β-Cyclodextrin and Hydroxypropyl-β-Cyclodextrin: Semi-Empirical Quantum Mechanical PM6 and PM7 Methods

Abstract: Molecular interactions of plumbagin inclusion complexes with β-cyclodextrin (BCD), dimethyl-β-cyclodextrin (MBCD), and hydroxypropyl-β-cyclodextrin (HPBCD) were investigated by semi-empirical, Parameterization Method 6 and 7 (PM6, and PM7) in the aqueous phase using polarizable continuum calculations. The results revealed two different binding modes of the plumbagin molecule inside the BCD cavity with a negative value of the complexation energy. In conformation-I, the hydroxyl phenolic group of plumbagin was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In another study, when compared to the experiment, PM3 provided wrong and at the same time opposite results to those obtained by PM7 [60]. To depict another example, in a study where β-CD, dimethyl-β-CD, and hydroxypropyl-β-CD were analyzed by both PM6 and PM7, in all cases PM7 delivered complexation energies of significantly lower values [58].…”
Section: Semi-empirical Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…In another study, when compared to the experiment, PM3 provided wrong and at the same time opposite results to those obtained by PM7 [60]. To depict another example, in a study where β-CD, dimethyl-β-CD, and hydroxypropyl-β-CD were analyzed by both PM6 and PM7, in all cases PM7 delivered complexation energies of significantly lower values [58].…”
Section: Semi-empirical Methodsmentioning
confidence: 96%
“…Similarly, as in the case of PM3, FT-IR spectra can be simulated [50,56]. Further, PM6 and PM7 are often combined with the DFT methods in form of the ONIOM approach [42, 52,57,58].…”
Section: Semi-empirical Methodsmentioning
confidence: 99%
“…We performed molecular dynamics simulations of plumbagin-BCDs inclusion com- Molecular docking and geometry optimization of plumbagin-BCDs inclusion complexes by semi-empirical quantum mechanical PM6 and PM7 methods were performed with a polarizable continuum model in the previous study. Two major stable conformations of inclusion complexes were selected (Figure 8C) [12]. In conformation-I, the methyl group of plumbagin is pointed toward the wider rim of the host molecule.…”
Section: Molecular Dynamics Simulations Of Inclusion Complexesmentioning
confidence: 99%
“…Recently researchers have reported that nano-encapsulation of plumbagin with β-cyclodextrin (BCD) can reduce toxicity and enhance pharmaceutical efficacy [9,10]. Our works have also reported the use of BCD and its derivatives to enhance the stability and aqueous solubility of plumbagin [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation